Subtitling Strategies in “The Boss Baby: Back in Business” Series - Muhammad Kholiq; Emrinne Agustine (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This research aims to find out the translation strategies in “The Boss Baby: Back in Business” series from the application called Netflix. This research uses descriptive qualitative method in which the data is collected in the form of words or pictures rather than numbers. The analysis of this research focuses on the translation strategies used in the web television series on Netflix. This research applies strategies of translation theory by Gottlieb to analyze the subtitle of the series. The result of this research shows that there are six strategies in the web television series entitled “The Boss Baby: Back in Business,” namely transfer strategy, decimation strategy, deletion strategy, paraphrase strategy, imitation strategy, and transcription strategy.